Hubungan antara Modified Glasgow Prognostic Score (mGPS) dengan Stadium dan Derajat Diferensiasi Kanker Ovarium - Irsan, Bob; Pradjatmo, Heru; Lutfi, Muhammad (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2020)
Background: Prognostic factors for ovarian cancer include residual tumor and chemotherapy response, but these parameters are not sufficient to predict ovarian cancer prognoses. A new approach such as mGPS that use a combination of CRP and albumin can be used to assess an inflammatory response. With mGPS, an elevated CRP value and hypoalbuminemia are poor prognosis.Â Objective: To investigate the effect of mGPS on histopathologic staging and grading of ovarian cancer.Method: The study design was a cross sectional study. The population of this study were patients with suspected ovarian cancer who underwent laparotomy surgical staging at RSUP Dr. Sardjito. The samples were patients with suspected ovarian cancer that have examined the hs-CRP level and albumin level preoperative,then underwent laparotomy surgical staging with histopathological results epithelial ovarian cancer. Data were analyzed using Chi Square test and logistic regression.Results and Discussion: there were 57 subjects with epithelial ovarian cancer consisting of 25 subjects (43.86%) with high mGPS and 32 subjects (56.14%) with low mGPS. The value of mGPS is associated with the stage of ovarian cancer (p = 0.000; RP = 4.000 CI 95% = 2.195 â€“ 7.289). The results of the multivariate analysis showed that the most important factor in determining the stage was mGPS (p = 0.000; RP = 3.818 95% CI = 1.544-6.092). While the most important factor in determining histopathologic grading of ovarian cancer was the type of ovarian tumor (p = 0.000; RP = 7.339 95% CI = 4.960-9.718).Conclusion: There was an association between mGPS and the stage of ovarian cancer. The histopathologic grading was not influenced by mGPS, but was influenced by the type of ovarian tumor.Keywords: mGPS; Stage; Histopathologic grading; Ovarian Cancer; Epithelial Type